Australian history in 7 questions - Hirst, J. B. (John Bradley), 1942- (Black Inc. Books, 2014)
'If there are genuine questions about Australian history, there is something to puzzle over. The history ceases to be predictable- and dull.'From the author of The Shortest History of Europe, acclaimed historian John Hirst, comes this fresh and stimulating approach to understanding Australia's past and present. Hirst asks and answers questions that get to the heart of Australia's history: Why did Aborigines not take up farming? How did a penal colony change peacefully into a democratic society? Why was Australia so prosperous so early? Why did the colonies federate? What effect did convict orig.